Knowledge and practices of primary health care workers related to the implementation of the revised infant and young child feeding policy 2013 in Blouberg Municipality, Capricon District, Limpopo Province - Mphasha, Mabitsela Hezekiel (My University, 2015)
Background: The revised Infant and Young Child Feeding Policy (IYCFP) 2013 encourages HIV-positive mothers to also exclusively breastfeed for six months, and to continue breastfeeding for a year with introduction of appropriate complementary feeding, while their children receive antiretroviral treatment. The aim of this study was to determine knowledge and practices of the Primary Health Care Workers (PHCWs) related to the implementation of the revised IYCFP 2013 in the Blouberg Municipality of Capricorn District, Limpopo Province. Methods: A quantitative descriptive study was conducted on 103 PHCWs. The questionnaire was closed ended. The questionnaire was developed based on the contents of the revised IYCFP 2013. A simple random sampling technique was used to sample nurses irrespective of the category. Data were analyzed through SPSS Software v23.0. Results: Most participants were females (91.3%), category were Professional Nurses (44.7%), aged between 31 and 40 years (44.7%) and also mostly worked for >10 years (56.3%). The results revealed that 97.1% of the participants have good knowledge about infant and young child feeding, 68% of participants were not trained on the revised IYCFP 2013, resulting to only 32% of participants having a good practice of this policy. Also 44.7% of the participants reported that they were not aware if clinics had a copy of this policy. The results further revealed that 92.2% of the participants reported that clinics still receive, keep and issue infant formula to HIV positive mothers, which maybe the reason the dieticians still receive requests for Infant Formulas to be delivered to HIV-positive mothers. Conclusion: There is a need for monitoring and evaluation to ensure availability and vi implementation of the revised IYCFP 2013; and also the need for in-service training on this policy in order to improve the capacity to implement the revised IYCFP 2013. Key Concepts Revised IYCFP 2013; knowledge; practice; implementation; PHCWs; infant and young child feeding.
Thesis (MPH.) -- University of Limpopo, 2015
Keywords: Infant and young child feeding; Primary Health Care Workers; Infant and Young Child Feeding Policy 2013; Rural health services; Primary health care -- South Africa -- Limpopo Province